2016
DOI: 10.1177/0042098016643303
|View full text |Cite
|
Sign up to set email alerts
|

Suburbanisation, homeownership aspirations and urban housing: Exploring urban expansion in Dar es Salaam

Abstract: This paper offers an exploration of urban expansion from the point of view of the individual residents buying land, settling and living in new, rapidly growing peripheral settlements of Dar es Salaam, Tanzania. The findings suggest that the demand for affordable housing is the primary motivation for residents moving to the periphery. The demand for self-built, owner-occupier housing is especially significant initially, while the demand for non-ownership housing increases in importance later in the process. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 39 publications
1
42
1
Order By: Relevance
“…Previous location, especially for those who most recently moved from outside the GKMA, was also not a significant predictor in any of the regression analyses. This is contrary to the findings of Andreasen et al (2017), who found that in Arusha (Tanzania), new migrants initially tend to settle in central areas of the city and are often renters. A possible explanation could be that, as various researchers have pointed out (e.g.…”
Section: Hypothesis 2: Housing Options Are Unequally Distributed Acrocontrasting
confidence: 99%
See 2 more Smart Citations
“…Previous location, especially for those who most recently moved from outside the GKMA, was also not a significant predictor in any of the regression analyses. This is contrary to the findings of Andreasen et al (2017), who found that in Arusha (Tanzania), new migrants initially tend to settle in central areas of the city and are often renters. A possible explanation could be that, as various researchers have pointed out (e.g.…”
Section: Hypothesis 2: Housing Options Are Unequally Distributed Acrocontrasting
confidence: 99%
“…Most urban areas experience rapid population growth, and Kampala is no exception: between 2002 and 2014, its population increased on average by 3 percent annually (Uganda Bureau of Statistics (UBOS), 2017), the population of its metropolitan area on average by 5.4 percent (SITU-Transitions, 2018). Meanwhile, the land area that can be classified as urban land in the Greater Kampala Metropolitan Area (GKMA) increased on average by 8 percent per annum between 2006and 2017(SITU-Transitions, 2018. This is in line with predictions by Angel et al (2011) who find that with a doubling of population, built-up area is expected to triple.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Transformation processes are characterized by incremental construction of residential housing, financed, built and inhabited by growing volumes of new residents. The new residents are of mixed ethnic origin, but predominantly long-term urban residents moving from central parts of the city (Andreasen and Agergaard, 2016). Their motivations for and aspirations towards settling in the periphery are shaped primarily by the search for affordable and comfortable housing, especially opportunities for self-built, owner-occupier housing .…”
Section: Data Collectionmentioning
confidence: 99%
“…While analyses of urban dynamics in Dar es Salaam (Andreasen & Agergaard, 2016;Andreasen, Agergaard, & Møller-Jensen, 2017b) have reported that the majority of urban residents plan their livelihoods disassociated from their rural connections, Mainet's analysis documents how urban residents are travelling to meet with their rural family on a regular basis. In the case of the secondary city of Bafoussam, up to 70% of these visits are related to farming and food supply, while in the primary city of Doula it is only the case for about 10% of visits.…”
Section: Urban Expansion and Changes In Rural-urban Land Usementioning
confidence: 99%